2013
DOI: 10.1073/pnas.1309576110
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 16 regulates innate immunity in response to epidermal barrier breach

Abstract: Mutations in the type I keratin 16 (Krt16) and its partner type II keratin 6 (Krt6a, Krt6b) cause pachyonychia congenita (PC), a disorder typified by dystrophic nails, painful hyperkeratotic calluses in glabrous skin, and lesions involving other epithelial appendages. The pathophysiology of these symptoms and its relationship to settings in which Krt16 and Krt6 are induced in response to epidermal barrier stress are poorly understood. We report that hyperkeratotic calluses arising in the glabrous skin of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
186
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(201 citation statements)
references
References 67 publications
14
186
0
1
Order By: Relevance
“…In contrast, we found no remarkable difference in Gsr mRNA ( Figure 1G). Although the mRNA levels of Me2 and G6pd were decreased 5.3 ± 0.2-fold and increased 3.7 ± 0.9-fold, respectively, the overall levels of NADPH were similar fragility (11). A follow-up effort showed that footpad lesions from Krt16 -/-mouse paw skin and biopsies from clinically involved plantar skin in individuals with PC show a remarkably similar molecular signature whereby the expression of genes coding for danger-associated molecular patterns (DAMPs), e.g., alarmins, and regulators of skin barrier formation, is markedly elevated (11).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, we found no remarkable difference in Gsr mRNA ( Figure 1G). Although the mRNA levels of Me2 and G6pd were decreased 5.3 ± 0.2-fold and increased 3.7 ± 0.9-fold, respectively, the overall levels of NADPH were similar fragility (11). A follow-up effort showed that footpad lesions from Krt16 -/-mouse paw skin and biopsies from clinically involved plantar skin in individuals with PC show a remarkably similar molecular signature whereby the expression of genes coding for danger-associated molecular patterns (DAMPs), e.g., alarmins, and regulators of skin barrier formation, is markedly elevated (11).…”
Section: Introductionmentioning
confidence: 89%
“…Although the mRNA levels of Me2 and G6pd were decreased 5.3 ± 0.2-fold and increased 3.7 ± 0.9-fold, respectively, the overall levels of NADPH were similar fragility (11). A follow-up effort showed that footpad lesions from Krt16 -/-mouse paw skin and biopsies from clinically involved plantar skin in individuals with PC show a remarkably similar molecular signature whereby the expression of genes coding for danger-associated molecular patterns (DAMPs), e.g., alarmins, and regulators of skin barrier formation, is markedly elevated (11). This effort also showed that subjecting clinically uninvolved skin in Krt16 -/-mice to wounding or topically applied chemical irritants results in an exaggerated upregulation of DAMP/alarmin and skin barrier genes relative to controls and, further, that Krt16 is an integral part of a strong genetic network involving such genes (11).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Keratins assemble as pairs, with keratin 16, the type 1 keratin partner of K6, required for the regulation of DAMP expression. 64 Specifically, K16 deficiency leads to cytokine and DAMP overexpression. It is therefore possible that extended expression of these 'wound-type' keratins in LPS-treated wounds may have evolved to suppress a heightened inflammatory response to skin bacteria upon injury.…”
Section: Oestrogen Restores Healing In Lps Model R Crompton Et Almentioning
confidence: 99%